2016
DOI: 10.1007/s10903-016-0532-x
|View full text |Cite
|
Sign up to set email alerts
|

Threat of Deportation as Proximal Social Determinant of Mental Health Amongst Migrant Workers

Abstract: While migration health studies traditionally focused on socioeconomic determinants of health, an emerging body of literature is exploring migration status as a proximate cause of health outcomes. Study 1 is a path analysis of the predictors of mental health amongst 582 documented migrant workers in Singapore, and shows that threat of deportation is one of the most important proximate social determinants of predicted mental illness, and a mediator of the impact of workplace conflict on mental health. Study 2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 26 publications
3
38
2
3
Order By: Relevance
“…Overall rates of psychological distress (21.9%) were slightly higher than what was previously found among non-injury or salary claim workers (13%) 13. Only 3% of our survey population were unemployed (eg, due to an injury-claim).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Overall rates of psychological distress (21.9%) were slightly higher than what was previously found among non-injury or salary claim workers (13%) 13. Only 3% of our survey population were unemployed (eg, due to an injury-claim).…”
Section: Discussioncontrasting
confidence: 73%
“…A large study on mental health in this vulnerable population in Singapore found an increased rate (62%) of psychological distress in migrant workers facing injury claims and salary disputes 13. In the larger Asian region, the few studies on the effects of economic migration on mental health have largely focused on the ‘left-behind’ families of migrant workers 14…”
Section: Introductionmentioning
confidence: 99%
“…All the participants in this study were documented migrant workers, which introduces another stability factor. Studies with undocumented workers (Meyer et al, 2016;Harrigan, Chiu, & Amirrudin, 2017;Reijneveld, de Boer, Bean, & Korfker, 2005;Vervliet, De Mol, Broekaert, & Derluyn, 2014;Vervliet, Lammertyn, Broekaert, & Derluyn, 2014) highlight the negative impact of legal insecurity on health outcomes and the increased risk that employers may use threats of deportation during workplace conflicts. Studies with migrant worker groups reporting high rates of alcohol overuse and abuse have also shown much higher rates of mental health problems (Ismayilova et al, 2014;Britto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Policies should build on evidence of the behaviour of migrants seeking healthcare and the consequences of poor health literacy, unawareness of rights, and language and cultural differences. Migrants may avoid seeking care for fear of arrest or deportation, or they may believe that they are “undeserving.”15 Discrimination and extortion by authorities, such as police or immigration officials, adds to migrants’ stress and discourages them from seeking care 16…”
Section: Overcoming Health Systems Barriersmentioning
confidence: 99%